PERENCANAAN STRATEGIS SISTEM INFORMASI MENGGUNAKAN METODE WARD DAN PEPPARD SERTA ANITA CASSIDY - Tiawan, Tiawan; Fajari, Muhamad Soleh; Mawarseh, Mawarseh; Novarini, Retno; Harahap, Ahmad Karim; Syastra, Muhammad Taufik; Khaerullah, Akbar; Kurniawan, Rifky; Maulid, Elfina; Irfayanti, Yulia; Sutrisno, Sutrisno; Wijayanti, Elisabeth Kurnia (Jurnal Informatika Teknologi dan Sains (Jinteks), 2024)
Innovation is needed in the era of global competition. To continue to grow, PT. China Taiping Insurance Indonesia must develop existing technology and information systems. Strategic planning is needed to realize the company's vision and mission and compete with competitors. Proper planning can also save costs in purchasing technology and information systems and renting services. Effectiveness and efficiency are important foundations for companies to run their business processes. As a general insurance company, PT. China Taiping Insurance Indonesia faces problems such as long insurance policy making, long risk acceptance, slow claim handling, inefficient accounting and financial processes, and time-consuming reinsurance grouping. To solve this problem, SWOT analysis is used to determine the company's strategic position as a basis for making a business strategy. Information is obtained from internal and external information flows using the Ward and Peppard and Anita Cassidy methods, with Critical Success Factors analysis from a SWOT perspective. The result is an application portfolio consisting of 9 applications in various strategic quadrants. This study produces IS business strategies, IT strategies, IS/IT management strategies, as well as recommendations for application portfolios, costs required, and implementation schedules that can be implemented at PT. China Taiping Insurance Indonesia.